2010
DOI: 10.1016/j.bbabio.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of OXPHOS by extramitochondrial calcium

Abstract: Despite extensive research, the regulation of mitochondrial function is still not understood completely. Ample evidence shows that cytosolic Ca2+ has a strategic task in co-ordinating the cellular work load and the regeneration of ATP by mitochondria. Currently, the paradigmatic view is that Cacyt2+ taken up by the Ca2+ uniporter activates the matrix enzymes pyruvate dehydrogenase, alpha-ketoglutarate dehydrogenase and isocitrate dehydrogenase. However, we have recently found that Ca2+ regulates the glutamate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 148 publications
8
89
0
2
Order By: Relevance
“…Thus, neurons could match or possibly anticipate the ATP consumption of ion pumps by using cytosolic Ca 2ϩ elevations to increase mitochondrial respiration (Gunter et al, 2004). Recently, a study of isolated brain mitochondria suggested that brain ATP production and thus CMRO 2 are controlled by a feedforward mechanism exclusively involving non-mitochondrial Ca 2ϩ (Gellerich et al, 2010). Furthermore, in isolated PCs in vitro, increased cytosolic Ca 2ϩ evoked by high extracellular K ϩ induced both mitochondrial depolarization due to mitochondrial Ca 2ϩ entry via the uniporter and an immediate burst in O 2 consumption (Hayakawa et al, 2005).…”
Section: Control Of Brain Energy Supply and Consumption By Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, neurons could match or possibly anticipate the ATP consumption of ion pumps by using cytosolic Ca 2ϩ elevations to increase mitochondrial respiration (Gunter et al, 2004). Recently, a study of isolated brain mitochondria suggested that brain ATP production and thus CMRO 2 are controlled by a feedforward mechanism exclusively involving non-mitochondrial Ca 2ϩ (Gellerich et al, 2010). Furthermore, in isolated PCs in vitro, increased cytosolic Ca 2ϩ evoked by high extracellular K ϩ induced both mitochondrial depolarization due to mitochondrial Ca 2ϩ entry via the uniporter and an immediate burst in O 2 consumption (Hayakawa et al, 2005).…”
Section: Control Of Brain Energy Supply and Consumption By Activitymentioning
confidence: 99%
“…In addition, respiration is controlled by the Ca 2ϩ -dependent mitochondrial aspartate-glutamate transporter, which increases mitochondrial nicotinamide adenine dinucleotide (NADH) levels (Satrú stegui et al, 2007). Indeed, recent studies suggest that glutamate-dependent oxidative phosphorylation in mitochondria is exclusively triggered by extramitochondrial Ca 2ϩ in physiological concentration ranges (Gellerich et al, 2010). Furthermore, rapid rises in oxygen consumption mediated by increased cytosolic Ca 2ϩ concentrations have been demonstrated in cultured Purkinje cells (PCs) (Hayakawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that Ca 2ϩ can influence AGC1 activity in rodent retinas we isolated mitochondria from rat retinas and measured their O 2 consumption over a range of free Ca 2ϩ concentrations using either glutamate and malate (Glu/Mal) or pyruvate and malate (Pyr/Mal) as fuel in a buffer containing EGTA. Oxidation of the Glu/Mal mix depends on AGC activity, whereas oxidation of the Pyr/Mal mix occurs independently of AGC1 (67). A, ADP was added at time 0 on this graph followed at 5 min (short dashed line) by either Pyr/Mal (black) or Glu/Mal (red) and then 20-nmol stepwise additions of CaCl 2 (longer dashed lines).…”
Section: Comparison With Earlier Studiesmentioning
confidence: 99%
“…The mitochondria produce ATP as a result of oxidative phosphorylation, they regulate intracellular Ca 2+ homeostasis and the production of reactive oxygen species (ROS) (Gellerich et al 2010, Moreira et al 2011. The mitochondria also play a key role in apoptotic processes (Moreira et al 2011).…”
Section: Introductionmentioning
confidence: 99%